IDENTIFIKASI MISKONSEPSI SISWA PADA PEMBELAJARAN KIMIA MENGGUNAKAN METODE FOUR-TIER DIAGNOSTIK TEST DI SMA NEGERI 03 KOTA BENGKULU - Rina Elvia; Trisan Amelia; Dewi Handayani (ALOTROP, 2022)
This research is a quantitative study that aims to find out misconceptions that occur in class X science students of SMAN 03 Bengkulu City on Stoichiometry material. The data obtained in this study were collected by means of a written test on an instrument that has been tested for validity, , reliability, difficulty index, and discriminatory power. The results of the analysis of the percentage of misconceptions that occur in the stoichiomeric material at SMAN 3 Bengkulu City are in the range of 0%-2,2%. Based on the literature, misconceptions with this number range are in the category of moderate misconceptions. The misconception with the smallest percentage value is in item number 2 with a percentage of 0,1%, namely in the sub-topic of Atomic Mass. The misconception with the most significant percentage figures occurs in questions number 9 and 10 or in the sub-chapter interconversion of moles and chemical calculations, which is 2,2%. Factors that cause misconceptions consist of internal factors caused by the students themselves, and external factors that cause environmental factors. These factors are wrong preconceptions or initial concepts, learning methods, student abilities, lack of interest and motivation to learn, wrong intuition, and inadequate books.